Experimental Investigation on PM10 and PM2.5 Concentrations in North Bandung - Wellid, Ismail; Nurfitriani, Nita; Falahuddin, Muhamad Anda; Simbolon, Luga Martin; Sunardi, Cecep; Nuryati, Neneng; bin Sukri, Mohamad Firdaus (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
North Bandung is an area where there are several tourist attractions, including the Dago Dream Park. The main road to several locations in North Bandung is via the road in front of Terminal Dago. For this reason, the purpose of this study was to collect data on PM2.5 and PM10 concentrations at both locations, namely in front of Terminal Dago and Dago Dream Park. Data collection was carried out for seven days, from Monday to Sunday, from 08.00 to 16.00 local time. To evaluate air quality in these two places, the national standard, namely PPRI No. 22 of 2021 and international standards from WHO were applied. The measurement results show that the concentrations of PM2.5 and PM10 in these two locations are still within the national standard. Meanwhile, when evaluated with WHO standards, PM10 concentrations in both locations are still within standard, but for PM2.5, there are several days where the air quality is out of the standard. The average concentrations of PM2.5 and PM10 during the 7 days of measurement at Terminal Dago are 19.9 μg/m3 and 21.6 μg/m3, respectively. While the average concentration of PM2.5 and PM10 during 1 week of data collection were 18.9 μg/m3 and 19.9 μg/m3, respectively. This means that the concentration of PM2.5 and PM10 at Terminal Dago is slightly higher than that of at Dago Dream Park. In addition, based on an evaluation using national standards, Dago Dream Park tourist attractions still have good air quality and are safe for local residents and tourists. From the data recorded at the Health Centre (Puskesmas), the number of ARI cases in the two locations in 2020 and 2021 is relatively not much different.